Tracking the impacts of innovation : offshore wind as a case study (International Renewable Energy Agency, 2021)
Clean energy technology innovation - particularly research, development and demonstration (RD&D) - plays a critical role in accelerating the global energy transition. As this transition progresses and ambitions grow, the need for strong government support for innovation grows alongside it. Innovation support is a combination of multiple measures, including RD&D funding (from the public and private sectors), market instruments and policy measures. Together, these guide and encourage innovation activities. This report from the International Renewable Energy Agency is an initial output of two interlinked projects focused on tracking innovation impacts: first, the Innovation Impacts Dashboard (IID) project - funded by the government of the United Kingdom - and second, the Tracking Energy Innovation Impacts Framework (TEIIF) project, funded by the Horizon 2020 Programme of the European Union (EU). Those projects both also contribute to the Mission Innovation Tracking Progress workstream. Offshore wind was chosen to pilot an initial methodology.